Evaluation of the driving effects of socio-economic development on soil erosion from the perspective of prefecture-level - Wang, Bing; Zeng, Yi; Li, Mengjie; Chen, Dan; Wang, Hanyu; Wang, Yunqi; Ni, Lingshan; Fang, Nufang (Frontiers in Environmental Science, 2022)
Soil erosion is affected by nature and human activities. Compared with biophysical factors, the effects of socio-economic factors on soil erosion have not been well investigated. Here, comparing two prefectures (Yan’an and Qingyang) with different socio-economic conditions and ecological restoration intensity on the Chinese Loess Plateau (CLP), we combined the Revised Universal Soil Loss Equation (RUSLE), partial least squares structural equation modeling (PLS-SEM), and gray relation analysis to explore how and what extent soil erosion responds to socio-economic development. Our results showed that Grain for Green Program (GGP) has significantly controlled soil erosion and increased the vegetation coverage of the study area. It achieved more significant effects in Yan’an with vegetation coverage increasing by 6.2% and erosion modulus decreasing by 33.9% from 1995 to 2015. Further statistical analysis indicated that the differences in industrial structure and agricultural input led to different responses of soil erosion to socio-economic development. Economic development and agricultural input accelerated soil erosion in Qingyang but inhibited soil erosion in Yan’an. Moreover, the increase of the gray relation grade between socio-economic factors and soil erosion in Yan'an indicates that soil erosion is easier to be controlled with the development of the socio-economy. The results indicate that the triple-win situation of economic development, vegetation restoration, and soil conservation can be realized by reasonably adjusting the economic structure and strengthening ecological restoration and agricultural investment. Our research could help determine the relationship between socio-economic development and ecological restoration and provide suggestions for ecological restoration and regional development.